Color duplex ultrasonography of temporal arteries: role in diagnosis and follow-up of suspected cases of temporal arteritis - Habib, Hisham M.; Essa, Ashraf A.; Hassan, Ayman A. (Clinical rheumatology, 2012)
The objectives of this study are to study the diagnostic value of color duplex ultrasonography (CDU) compared with the clinical results and temporal artery biopsy (TAB) in patients with suspected temporal arteritis (TA) and evaluate the prognostic value of CDU in follow-up of patients of sure diagnosis of TA under treatment in correlation to clinical response. The study included 32 consecutive patients of clinically suspected TA, and 30 age- and gender-matched control subjects. Baseline clinical characteristics and bilateral CDU of temporal arteries were performed to all subjects. CDU aimed to assess presence of a dark halo around the arterial lumen (a halo sign) or presence of stenoses and occlusions of temporal arteries. Unilateral TAB was performed then in all patients but not in control subjects. Subsequent CDU examinations were performed at 2, 4, 8, and 12 weeks after onset of treatment in patients with abnormal CDU. A halo sign at baseline CDU was evident in 13 TA patients (81%) and in 2 non-TA patients (12%) but none in control subjects. The presence of a halo sign in total yielded 81% sensitivity and 88% specificity whereas the presence of bilateral halo sign yielded 37% sensitivity and 100% specificity. Subsequent CDU examinations of TA patients showed disappearance of a halo sign in nine patients at 2 weeks and in four patients at 4 weeks with a mean of disappearance of 21 days after initiation of treatment. CDU is non-invasive, easy, and inexpensive method for diagnosis of TA. It is of higher sensitivity and specificity. It can be used in combination with clinical and laboratory tools for diagnosis of TA. It can effectively predict which patient will need TAB. In patients with bilateral halo sign, TAB is not necessary.